Difficulties of access to public health care as perceived by mothers of type 1 diabetic adolescents - Lívia de Paulo Pereira; Maria Vilani Cavalcante Guedes (Rev Rene)
The objective of this descriptive and exploratory study was to evaluate the difficulties of access to public health care services as perceived by mothers of type 1 diabetic adolescents. Data collected between March and May 2006 through semi-structured interviews with 25 mothers of diabetic adolescents aged 10 to 19 years of age attending a referral facility Center were submitted to Bardin’s content analysis. The mothers reported difficulties of access to diagnosis. The cooperation between health care services at different levels through an efficient referral and counter-referral system has been shown to improve the quality of health care. However, due to the administrative inefficiency of primary health care facilities in Brazil, diagnosis is delayed, users are fatigued and patients are exposed to greater risk of complications.